Colonic Polyps: Diagnosis and Surveillance - Huck, Michael B.; Bohl, Jaime L. (Clinics in Colon and Rectal Surgery, 2016)
Colorectal cancer begins as a polyp that is a benign growth on the mucosal surface of the colon or rectum. Over a period of 5 to 15 years, polyps can degenerate into a cancer, thus invading the colonic wall. Colorectal screening methods are designed to diagnose and remove polyps before they acquire invasive potential and develop into cancer. Screening for colorectal cancer can prevent and reduce mortality. Given the benefits and effectiveness of screening, guidelines exist from multiple organizations. These guidelines risk-stratify patients to determine the age of screening initiation and the interval for repeat screening. Categories of colorectal cancer risk include average risk, increased risk, and high risk based on individual and family medical history. Screening methods vary widely in the ability to diagnose and treat polyps and in the degree of invasiveness or risk of complication to the patient. Colonoscopy is held as the “gold standard” by which all other methods are compared; however, less-invasive modalities including computed tomographic colonography are increasing in popularity.
Keywords: colorectal polyps; colonoscopy; colorectal screening; CT colonography